Rancang Bangun Monitoring Kondisi Baterai dan Lokasi Kendaraan Listrik Berbasis Mikrokontroler Esp32 - Resa Falentino; Rizki Priya Pratama (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Electric Vehicles Require A Reliable Monitoring System To Maintain Their Efficiency And Safety. This Study Designs A Monitoring System For Battery Condition And Vehicle Location Based On The Esp32 Microcontroller And The Mit App Inventor Application. The System Uses The Pzem 017 Sensor To Monitor Voltage, Current, Power, Energy, As Well As Battery Capacity And Health, And The Neo-7m Gps Module For Location Tracking. Data Is Displayed In Real Time Through An Android Application. Test Results Show That The System Provides Accurate Information, With Minimal And Statistically Insignificant Measurement Errors According To The Paired T-Test. The System Also Remains Stable At Various Vehicle Speeds (Anova), And The Location Tracking Demonstrates An Average Accuracy Of 4.77 Meters In Open Areas. In Enclosed Areas, The Error Increases To An Average Of 10.26 Meters. The System Is Also Capable Of Automatically Calculating Battery Capacity And Health. Overall, The Developed System Proves To Be Effective, Efficient, And Flexible In Supporting The Reliability And Safety Of Electric Vehicles.